2016
DOI: 10.12693/aphyspola.130.428
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Source, an Important Determinant of Fatty Acid Accumulation and Profile in Scenedesmus obliquus

Abstract: The potential of algae-based fuel technologies for manufacturing renewable biofuels has been attracting interest from the scientific community. Biomass productivity and cellular lipid content are important parameters affecting the feasibility of using algae oil for biodiesel production. This study compares utilization of NaNO3, NH4Cl and urea as different nitrogen sources in terms of their effects on biomass productivity, fatty acid profile and accumulation in Scenedesmus obliquus. Cellular lipid accumulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…However, Yilancioğlua et al [14] reported that Scenedesmus obliquus cultured with nitrates grew higher than when cultured with ammonia or nitrites. Moreover, a study on the effects of different nitrogen sources in 10 species of phytoplankton found that 2 species (Hillea sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Yilancioğlua et al [14] reported that Scenedesmus obliquus cultured with nitrates grew higher than when cultured with ammonia or nitrites. Moreover, a study on the effects of different nitrogen sources in 10 species of phytoplankton found that 2 species (Hillea sp.…”
Section: Discussionmentioning
confidence: 99%
“…Fidalgo et al [13] cultured Isochrysis galbana with different nitrogen sources which grew with nitrates or nitrites, showing that the fatty acids were very similar at any stage of growth, but were slightly different from the urea-grown cells; and Isochrysis cultured in the urea media had the highest saturated and monounsaturated fatty acids. The results from the study of Yilancioğlua et al [14] showed that sodium nitrate, ammonium chloride, and urea could be successfully utilized for the growth of the green algae Scenedesmus obliquus, and found that ammonium chloride resulted in increased lipid accumulation when compared to alternative nitrogen sources such as sodium nitrate and urea.…”
Section: Introductionmentioning
confidence: 99%
“…Short-chain fatty acids (SCFAs) are saturated fatty acids featuring an aliphatic chain length of at most eight carbon atoms [22]. The fermentation of the different dietary fibres leads to an increase in concentrations of several short-chain fatty acids, especially butyrate, propionate, and acetate, in the lumen of the proximal regions of the large intestine [23].…”
Section: Short-chain Fatty and Probioticsmentioning
confidence: 99%
“…Biodiesel has recently been paid attention since it is one of the sustainable energy resources [2]. Although the homogeneous catalysts can be used for biodiesel synthesis, the separation of the reaction components and the catalyst from the reaction mixture is difficult and also energy consuming, even if a high yield can be obtained [3,4].…”
Section: Introductionmentioning
confidence: 99%